ANALISIS BIAYA EFEKTIF TERAPI SKABIES PERMETRIN 5% DAN SALEP 2-4 - Nuri Handayani; Lingga Ikaditya (Media Informasi, 2019)
Scabies is a skin disease caused by Sarcoptes scabiei infection. The World Health Organization (WHO) estimates that the world incidence is 0.2-24%, Indonesia has a high prevalence of scabies, at any age. Research Objectives: The object of this study is to compare the cost-effectiveness of permethrin 5% with Unguentum 2-4 in patients with scabies.  Research Type : The research type of this study is Cost-Effectiveness Analysis, the population in this study were students who diagnosed with scabies in Miftahul Huda Islamic boarding school. The sample recruited were 21 patients. Research Results: The analysis of Average Cost Effectiveness (ACER) and Additional Cost Effectiveness Ratio (ICER) performedand show the use of Unguentum 2-4 is more effective than Permethrin 5%. The score of ACER Unguentum 2-4 is 521,978, while Permethrin 5% is 841,837. ICER value is Rp. 5,000 for an increase of 1 unit effectivity of Permethrin 5%toUnguentum 24. Keywords: Permethrin 5%, Unguentum 2-4, ACER, ICER